Cytorhabdovirus P3 genes encode 30K-like cell-to-cell movement proteins - Mann, Krin S.; Bejerman, Nicolas Esteban; Johnson, Karyn N.; Dietzgen, Ralf Georg (2017)
Plant viruses encode movement proteins (MP) to facilitate cell-to-cell transport through plasmodesmata. In this study, using trans-complementation of a movement-defective turnip vein-clearing tobamovirus (TVCV) replicon, we show for the first time for cytorhabdoviruses (lettuce necrotic yellows virus (LNYV) and alfalfa dwarf virus (ADV)) that their P3 proteins function as MP similar to the TVCV P30 protein. All three MP localized to plasmodesmata when ectopically expressed. In addition, we show that these MP belong to the 30K superfamily since movement was inhibited by mutation of an aspartic acid residue in the critical 30K-specific LxD/N50–70G motif. We also report that Nicotiana benthamiana microtubule-associated VOZ1-like transcriptional activator interacts with LNYV P3 and TVCV P30 but not with ADV P3 or any of the MP point mutants. This host protein, which is known to interact with P3 of sonchus yellow net nucleorhabdovirus, may be involved in aiding the cell-to-cell movement of LNYV and TVCV.